Effect of Temperature and Potassium Chloride Impurity on the Relative ⟨101̅0⟩ Tilt Grain Boundary and Surface Free Energies in Ice - Di Prinzio, Carlos Leonardo (2014)
The ratio of the grain boundary free energies relative to the surface free energies γgb/γs can be determined by measuring the root angles of the grooves formed at the intersection of the grain boundary with the free surface. The grooves were copied by plastic replicas, and the topographic details were revealed with a laser confocal 3D microscope. Values of γgb/γs were determined for high purity and potassium chloride doped ice bicrystals annealed at −5 and −18 °C. The studied samples were ⟨101̅0⟩/ψ tilt grain boundaries with ψ between 10 and 180°. The used KCl concentrations were 1 and 10 μmol/l, and the conductivity of the pure ice was 0.3 μS. ⟨101̅0⟩/60° grain boundary relative energies were also determined for different grain boundary inclinations. All the γgb/γs obtained values were analyzed and compared using the CSL (coincidence site lattice) theory. For pure samples annealed at −18 °C, an important variation of γgb/γs with the grain boundary inclination was found. In general, a remarkable correspondence between CSL planar density Γ and γgb/γs was observed. Results also showed that the increase of temperature and the impurity changes significantly γgb/γs.